Economic Inequalities in India: Some Disquieting Features - Cheema, Maninder Deep; Singh, Jagsir; Singh, Jatinder (International Journal of Psychosocial Rehabilitation, 2019)
The paper aims at investigating the nature and extent of economic inequality in India in the post reform period. Recent evidence suggests that economic inequality has been steadily rising in India since the onset of economic liberalization. For this, secondary information has been collected and analysed using various quantitative techniques. Results suggest that inequalities across the globe have drastically increased during 1980 to 2016, but situation is very grim in case of India. Analysis reveals that income share of top 1 per cent witnessed a continuous decline till early 1980s whereas it started rising since the mid-1980s. Since the early 2000s, the income share of top 1 per cent population in India has reached above the income share of bottom 50 per cent. Inequalities are not only limited to income distribution, but also very sharp in terms of consumption expenditure and assets holding. During 1991 to 2012, the share of bottom 30 per cent population in total private wealth declined from 2.8 per cent to 1.33 per cent, whereas, the share of top 10 per cent has increased from 51.6 per cent to 62.5 per cent. It is clear that benefits of economic growth in India have beenenjoyed by the rich, rather than percolating down to improve the economic health of poor in the phase of high economic growth. Key words: inequalities, assets, consumption expenditure, reforms, growth.